Mental health symptoms in German elite athletes: a network analysis - Geiger, S.; Jahre, L.; Aufderlandwehr, J.; Krakowczyk, J. B.; Esser, A. J.; Mühlbauer, T.; Skoda, E.; Teufel, M.; Bäuerle, A. (Frontiers in Physiology, 2023)
Introduction: Elite athletes are exposed to a variety of sport-specific stressors that may put them at particular risk for mental health symptoms and disorders. The aim of the present study was to assess data on mental health of elite athletes and investigate associations and interconnections among different variables using network analysis.